MAT learners for recognizable tree languages and tree series - Drewes Frank; Weighted Automata : Theory and Applications (2008) (Dresden) (2009)
We review a family of closely related query learning algorithms for unweighted and weighted tree automata, all of which are based on adaptations of the minimal adequate teacher (MAT) model by Angluin. Rather than presenting new results, the goal is to discuss these algorithms in sufficient detail to make their similarities and differences transparent to the reader interested in grammatical inference of tree automata.
Keywords: Természettudományok; Számítás- és információtudomány